Myocardial infraction – the history of therapy prior to reperfusion - Fiałek, Bartosz; Zukow, Walery (Journal of Education, Health and Sport, 2018)
The description of stenocardial ailments was presented for the first time in 1772. Until the 1950s, the patients suffering from myocardial infraction were treated with the wait-and-see attitude – they were confined to bed for 6 weeks, were not allowed to eat or to take up everyday activities on their own. It was as late as in the 1960 it was discovered that being immobilised for too long may be harmful and lead to the increase of the clotting/embolism complications. The first issue of Harrison’s Principles of Internal Medicine was released in 1950 which advised the oxygen therapy, as well as pharmacotherapy (nitro-glycerine, anticoagulants) used in the severe phase of myocardial infraction. One on the breaking moments on the path of the development of care considering the patient with myocardial infraction was the introduction of CCU (Desmond Julian, 1961).